Unexpected Vertical Transmission of SARS-CoV-2: Discordant Clinical Course and Transmission from Mother to Newborn - Alessandra Boncompagni; Mattia De Agostini; Licia Lugli; Giliana Ternelli; Valeria Colonna; Emanuela Biagioni; Maria Paola Bonasoni; Tiziana Salviato; Liliana Gabrielli; Mirella Falconi; Fabio Facchinetti; Alberto Berardi (Microorganisms, 2022)
Mother-to-newborn COVID-19 transmission is mainly postnatal, but single-case reports and small case series have also described SARS-CoV-2 transplacental transmission. Unfortunately, studies regarding vertical transmission of SARS-CoV-2 lack systematic approaches to diagnosis and classification. So far, scientific evidence seems to suggest that the severity of maternal infection increases the risk of vertical transmission. We report two neonates born from COVID-19-positive mothers, of which one of the newborns had a vertical infection. The placental involvement, and consequent intrauterine transmission of SARS-CoV-2, were inversely related to the severity of the maternal disease. The description of cases divergent from current evidence on this topic could provide new insights to better understand SARS-CoV-2 vertical transmission.